STING Agonists and How to Reach Their Full Potential in Cancer Immunotherapy - Laura Gehrcken; Christophe Deben; Evelien Smits; Jonas R.M. Van Audenaerde (Advanced Science)
Abstract As cancer continues to rank among the leading causes of death, the demand for novel treatments has never been higher. Immunotherapy shows promise, yet many solid tumors such as pancreatic cancer or glioblastoma remain resistant. In these, the “cold” tumor microenvironment with low immune cell infiltration and inactive anti‐tumoral immune cells leads to increased tumor resistance to these drugs. This resistance has driven the development of several drug candidates, including stimulators of interferon genes (STING) agonists to reprogram the immune system to fight off tumors. Preclinical studies demonstrated that STING agonists can trigger the cancer immunity cycle and increase type I interferon secretion and T cell activation, which subsequently induces tumor regression. Despite promising preclinical data, biological and physical challenges persist in translating the success of STING agonists into clinical trials. Nonetheless, novel combination strategies are emerging, investigating the combination of these agonists with other immunotherapies, presenting encouraging preclinical results. This review will examine these potential combination strategies for STING agonists and assess the benefits and challenges of employing them in cancer immunotherapy.